The Effect of Using Quizizz Web-Based Learning Media on Students’ Grammar Inquiry at SMA Negeri 1 Situbondo - M. Hilmy Hidayatullah; Khalidatul Fajriyah Syaiful (LP2M Universitas Ibrahimy, 2024)
One of learning application that is commonly used in learning English is Quizizz. The purpose of this study is to determine the effect of Quizizz web-based learning media on students’ grammar inquiry. This research used quasi experimental research. The data collection method used was pre-test and post-test of grammar. The sample of this research was class XII MIPA 1 which consisted of 31 students and XII MIPA 2 which consisted of 34 students. The research variable was the Quizizz web-based learning media as independent variable and students’ grammar inquiry as dependent variable. The findings indicated that the mean score of the students’ before using Quizizz web-based learning media got 51.25 in experimental group and got 55.71 in control group. The mean score after using Quizizz web-based learning media was 77.68 in experimental group and 75.36 in control group. This educational research uses 5% significance level. The t-test analysis is used in this research based on the sample size that is below 30 samples with t-score 1.729. based on output pair 1 on table 4.6, t value 0.184 < 1.729, there is no difference between the average student learning outcomes for the experimental group post-test and control group post-test. So, it can be concluded that there is no effect of using Quizizz web-based learning media on students’ grammar inquiry.